THE EFFECT OF MARKETING MIX ON PATIENT SATISFACTION IN THE REGIONAL TECHNICAL IMPLEMENTATION UNIT OF THE REGIONAL HEALTH LABORATORY OF BONDOWOSO DISTRICT - Luki Herli Purniawan; Agustin Hari Prastyowati; Hary Sulaksono (MBA - Journal of Management and Business Aplication, 2023)
Laboratory services are an integral part of health services that are needed to support healthimprovement, prevention, treatment, as well as health restoration. UPTD LabkesdaBondowoso is a Health Laboratory that plays a role in health development services asCommunity Health Efforts (Indonesian: UKM) and Individual Health Efforts (Indonesian:UKP) to support various health programs. UPTD Labkesda Bondowoso needs to improve itsmarketing strategy in providing satisfaction for patients. This research aims to determine theeffect of the marketing mix (product, price, place, people, promotion, process, and physicalevidence) on the satisfaction of patients receiving services from the UPTD Labkesda,Bondowoso District. This research is descriptive quantitative research. The analyticalmethods used are linear regression analysis, classical assumption test (multicollinearity test,heteroscedasticity test, and normality test). Data collection is done by using observation,questionnaires, and direct interviews. The number of samples is 357 and the number ofpopulations is about 3,320 patients in several hospitals in Bondowoso District. This researchuses the Product, Price, Place, People, Promotion, Process and Physical Evidence as theindependent variables and patient satisfaction as the dependent variable. The results showthat product, Price, Place, People, Promotion, Process, and Physical Evidence have asimultaneous effect on patient satisfaction. Partially, Product, Price, Place, People, andPhysical Evidence have no significant effect on patient satisfaction. The Promotion is theonly variable that has a significant effect on patient satisfaction.